How hot is .brussels? Analysis of the uptake of the .brussels top-level domain name extension - Margot Waty; Seth van Hooland; Simon Hengchen; Mathias Coeckelbergs; Max De Wilde; Jean-Michel Decroly (Brussels Studies, 2018)
The opening up of the top-level domain name market in 2012 has offered new perspectives for companies, administrations and individuals to include a geographic component within the domain name of their website. Little to no research has been carried out since then to analyse the uptake of the new top-level domain names (TLDNs). Based on the specific case of the TLDN .brussels, this article proposes an empirical study of how the opening up of the top-level domain name market actually impacts registration practices. By making use of freely available software tools such as OpenRefine and Natural Language Processing (NLP) methods, the entire corpus of the .brussels domain names (6 300) was analysed from a quantitative perspective. Based on a statistically representative sample (592 domain names), a qualitative interpretation allowed a more fine-grained analysis of how the new TLDN is being used in practice. By doing so, the article gives detailed insight into the impact of the recent changes to the rules concerning domain name registration. Through this analysis, researchers, policy makers, investors and anyone concerned about the identity of Brussels in the digital realm may have a better understanding of the state of play of the .brussels TLDN.